Inhibition of Staphylococcus aureus by garlic and NaCl in broth systems - Bayani, Monalisa M.; Azanza, Ma. Patricia V. (Quezon City College of Home Economics, University of the Philippines Diliman, 2004)
Minimum inhibitory concentration (MIC) isobolograms of fresh garlic extract (FGE) and NaCl against Staphylococcus aureus test strains ATCC 25923 and ATCC 6538 in Brain Heart Infusion broth (BHIB) and Pork Sausage broth (PSB) were constructed. Additive and synergistic relationships were observed in BHIB and PSB against the test strains, respectively. Action of indirect antimicrobic ingredients in PSB was used to explain the synergistic relationship of FGE and NaCl established. The Fractional Inhibitory Concentration (FIC) indices of the agents validated the antimicrobic relationships established in the MIC isobolograms. An Iodonitroterazolium-Direct Microscopic Count (INT-DMC) mehtod was used to measure staphylococcal cell count reductions used in sausage production. Garlic incorporation of >= 1.20% (v/v) together with minimum levels of NaCl (<2% w/v) can be recommended in cured pork sausage formulations for control of staphylococcal growth.
Thesis (Master of Science in Food Science)--University of the Philippines Diliman
Keywords: Garlic; Salt; Meat -- Effect of salt on